PENGARUH SPIRITUAL LEADERSHIP DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN BANK MUAMALAT CABANG PADANG - Retha Dwiyanti Putri Anhar (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2020)
This type of research is descriptive quantitative because it aims to get a picture of conditions and situations in the work environment of employees of Bank Muamalat Padang Branch related spiritual leadership, work motivation and job satisfaction and how the influence of each variable. The sample of this study using total sampling that 71 people so that the method used is census method by spreading the questionnaire. Hypothesis testing is done by using SPSS version 22. The result of multiple regression analysis shows the relationship between each independent variable to the dependent: spiritual leadership and work motivation have a positive and significant effect on employee job satisfaction. The result of coefficient of determination (R2) test shows that R2 equal to 0,470 means that the contribution of influence to employee job satisfaction is 47 % while the rest is influenced by other variables like leadership, work motivation and compensation. Managerial implications that writers can ask is if the company wants to improve employee satisfaction then the company must first improve spiritual leadership, so employee satisfaction is achieved. Furthermore, the company can increase employee work motivation in working to maximize employee job satisfaction. Keywords: Spiritual Leadership, Work Motivation, Job Satisfaction, Sharia Bank